2016
DOI: 10.1111/inm.12189
|View full text |Cite
|
Sign up to set email alerts
|

Physical health and well‐being: Experiences and perspectives of young adult mental health consumers

Abstract: Compromised physical health and raised levels of morbidity and mortality are experienced by young people (16-24 years) with mental illness, and are compounded by psychotropic medication. How this group conceives and experiences physical health is not well understood. We investigated the meanings, beliefs, and endeavours of young people that impact their physical health understandings and behaviours. The present study formed the qualitative phase of a sequential mixed-methods study, and incorporated semistructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 34 publications
0
28
0
3
Order By: Relevance
“…Through this programme, the young adults gained structure and support, findings that are in line with previous research (McCloughen et al . ). Some participants found the cognitive support (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Through this programme, the young adults gained structure and support, findings that are in line with previous research (McCloughen et al . ). Some participants found the cognitive support (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Through participating in the KBIM programme, young people participants in this study related how they had improved their skills and knowledge about what constitutes a healthy lifestyle and adopting new behaviours . In previous research, young adult mental health consumers identified that they lacked knowledge and motivation to address the considerable negative impact on their physical health that accompanied development of a mental illness (McCloughen et al ). The present study showed that providing young adults with a lifestyle intervention was an enabling factor for them to take control of their physical health.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy related to mental, physical, and metabolic health care influences health behaviours and health outcomes (Gulliver et al 2010;McCloughen et al 2016). An increase in knowledge and understanding of health and health care can enable the young person to make better lifestyle choices and build their confidence and trust to work collaboratively with health professionals, including their peer support workers to improve physical healthcare outcomes (Young et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While there is a plethora of literature on the poor physical health outcome of adults with mental illness (Curtis et al 2011;McCloughen et al 2016;Morrison et al 2015), the literature is now highlighting the physical health issues affecting young people diagnosed with first-episode psychosis (Bradshaw & Pedley 2012;Hetrick et al 2010;Malla et al 2016). Furthermore, young people do not always have awareness early in their illness trajectory about the impact their psychosis and the antipsychotic medications they receive as treatment can have on their physical health into the future (Morrison et al 2015).…”
Section: Introductionmentioning
confidence: 99%